High-purity quartz fiber electronic cloth and its preparation method
Patent Information
- Application Number
- CN202611079164.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
AI Technical Summary
主要通过双硅烷偶联剂在石英纤维表面构建高交联密度的三维Si-O-Si网络结构,并结合等离子体活化引入极性官能团和表面微粗糙度,两者协同作用显著增强了石英纤维与树脂基体之间的界面结合能力,解决复合材料界面结合力弱、易分层的问题
1、本发明通过双硅烷偶联剂预处理和等离子体活化协同处理,使石英纤维电子布界面剪切强度(ILSS)得到大幅提高。实施例1的ILSS达到48.5 MPa,相比未处理的对比例8(10.2 MPa)提高375%;相比常规单硅烷处理的对比例5(25.6 MPa)提高89%。充分证明本发明构建的三维交联界面层与等离子体活化之间的协同增效作用。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials technology, and in particular to a high-purity quartz fiber electronic cloth and its preparation method. Background Technology
[0002] Quartz fiber electronic cloth is a high-performance electronic material made of high-purity quartz. It possesses excellent properties such as low dielectric constant, low dielectric loss factor, and low coefficient of thermal expansion, while also exhibiting high-temperature resistance, ablation resistance, chemical stability, and good mechanical properties. It is widely used in high-frequency communication equipment, high-speed computing equipment, radar radomes, and other fields.
[0003] However, in the application of quartz fiber electronic cloth reinforced resin matrix composites, interfacial bonding performance is a key factor determining the overall performance of the composite material. The weak wettability and chemical bonding between quartz fibers and the organic resin matrix make the composite material prone to interfacial debonding and delamination failure during use. This problem severely restricts the application of quartz fiber reinforced resin matrix composites in high-end fields such as high-performance electronic substrates and aerospace structural components.
[0004] Therefore, there is an urgent need for a high-purity quartz fiber electronic cloth with excellent interfacial bonding performance to meet the needs of practical applications. Summary of the Invention
[0005] In view of this, the present invention proposes a high-purity quartz fiber electronic cloth and its preparation method. The method mainly involves constructing a high-crosslink density three-dimensional Si-O-Si network structure on the surface of quartz fibers using a bissilane coupling agent, and combining this with plasma activation to introduce polar functional groups and surface micro-roughness. The synergistic effect of these two methods significantly enhances the interfacial bonding ability between the quartz fibers and the resin matrix, solving the problems of weak interfacial bonding and easy delamination in composite materials.
[0006] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a method for preparing high-purity quartz fiber electronic cloth, comprising the following steps: S1, immerse the quartz fiber electronic cloth in a silane coupling agent hydrolysis solution, remove it and perform heat treatment to obtain the pretreated quartz fiber electronic cloth; S2, the pretreated quartz fiber electronic cloth is subjected to plasma treatment; S3 involves combining plasma-treated quartz fiber electronic cloth with a resin matrix to obtain high-purity quartz fiber electronic cloth.
[0007] Based on the above technical solutions, preferably, in step S1, the components of the silane coupling agent hydrolysis solution include a silane coupling agent containing at least two trialkoxysilane groups.
[0008] Pretreatment of the bissilane coupling agent enables the bissilane group coupling agent to form a high cross-linking density coupling layer with a three-dimensional Si-O-Si cross-linking network on the surface of quartz fiber through multi-point anchoring and intermolecular condensation reaction of its six hydrolyzable alkoxy groups.
[0009] Based on the above technical solutions, preferably, the silane coupling agent includes one or both of BTSE (1,2-bis(triethoxysilyl)ethane) and BSA (bis[3-(trimethoxysilyl)propyl]amine). More preferably, the silane coupling agent includes BTSE and BSA.
[0010] The molecular structure of BTSE contains an ethylene bridge (-CH2CH2-) and six hydrolyzable ethoxy groups (-OCH2CH3). After hydrolysis, it forms a high-density Si-O-Si three-dimensional cross-linked network through the condensation of six silanol groups (Si-OH) under pH 4.0 conditions. The molecular structure of BSA contains a secondary amino group (-NH-) and six hydrolyzable methoxy groups (-OCH3), and it has both multi-point anchoring and resin reactivity.
[0011] Based on the above technical solutions, preferably, the total mass concentration of the silane coupling agent is 1~3 wt%. More preferably, the total mass concentration of the silane coupling agent is 2.5 wt%.
[0012] Based on the above technical solutions, preferably, the mass ratio of BTSE to BSA is 1 to 3:1. More preferably, the mass ratio of BTSE to BSA is 2:1.
[0013] Based on the above technical solutions, preferably, the preparation of the bissilane coupling agent hydrolysis solution includes the step of adding the silane coupling agent to an ethanol solution for hydrolysis.
[0014] Based on the above technical solutions, preferably, the pH of the alcohol-water mixed solvent is 3.5~5.0, and the hydrolysis conditions are hydrolysis at 15~40℃ for 30~90 min.
[0015] Based on the above technical solutions, a further preferred method is to add the silane coupling agent to a 75% (v / v) ethanol aqueous solution, adjust the pH to 4.0, and hydrolyze it at 25°C for 60 min.
[0016] Based on the above technical solutions, preferably, in step S1, the quartz fiber electronic cloth also undergoes cleaning pretreatment and drying treatment; the heat treatment temperature is 80~150℃ and the time is 0.5~3h. More preferably, the heat treatment temperature is 120℃ and the time is 1.5h.
[0017] The quartz fiber electron array is ultrasonically cleaned in a cleaning solution for 10–30 minutes to remove organic contaminants and impurities from the fiber surface. It is then rinsed with deionized water and dried at 80–120°C for 1–3 hours. The cleaning solution is any one of acetone, ethanol, or a mixture of acetone and ethanol.
[0018] Based on the above technical solutions, preferably, in step S2, the plasma treatment includes arranging pretreated quartz fiber electrons in a plasma treatment device, introducing a working gas under a vacuum of 1~1000 Pa, and performing plasma treatment with a treatment power of 100~300W and a time of 10~30min. More preferably, the plasma treatment power is 200W and the time is 20min.
[0019] Plasma surface activation can introduce polar oxygen-containing functional groups such as -OH and -COOH onto the surface of high cross-linking density coupling layers and moderately increase the surface micro-roughness, thus compensating for the limited reactivity of the bissilane coupling layer towards the resin side and enhancing the wettability and chemical bonding ability of the coupling layer to the resin matrix.
[0020] Based on the above technical solutions, preferably, in step S3, the resin matrix includes any one of epoxy resin, cyanate ester resin, silane-containing resin, bismaleimide resin, and polyimide resin.
[0021] Secondly, a high-purity quartz fiber electronic cloth is provided, which is prepared by the preparation method of high-purity quartz fiber electronic cloth as described above.
[0022] The high-purity quartz fiber electronic cloth and its preparation method of the present invention have the following advantages over the prior art: 1. This invention significantly improves the interfacial shear strength (ILSS) of quartz fiber electronic cloth through a synergistic treatment of pretreatment with a bissilane coupling agent and plasma activation. The ILSS of Example 1 reached 48.5 MPa, a 375% increase compared to the untreated Comparative Example 8 (10.2 MPa), and an 89% increase compared to the conventionally monosilane-treated Comparative Example 5 (25.6 MPa). This fully demonstrates the synergistic effect between the three-dimensional cross-linked interface layer constructed in this invention and plasma activation.
[0023] 2. At high frequencies (10 GHz), the high-purity quartz fiber electronic cloth composite material treated by this invention still maintains a low dielectric constant (Dk ≤ 3.28) and a low dielectric loss factor (Df ≤ 0.0054). In particular, the Df of Example 1 is as low as 0.0048, which is better than the 0.0095 of the untreated sample. This shows that the method of this invention strengthens the interface without introducing too many polar groups or defects. Instead, it reduces dielectric loss by reducing interfacial voids and microcracks, thus meeting the stringent requirements for low-loss materials in high-frequency communication, radar radomes, and other applications. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] The silane coupling agents BTSE and BSA used in this invention were purchased from Nanjing Nengde Chemical Co., Ltd., and the quartz fiber electronic cloth was purchased from Hubei Feilihua Quartz Glass Co., Ltd. The SiO2 content in the quartz fiber is ≥99.95%, and the remaining reagents and materials are all conventional commercially available products.
[0026] Example 1 Pre-treatment of quartz fiber electronic cloth cleaning: Take the quartz fiber electronic cloth, place it in acetone and ultrasonically clean it for 20 minutes. After taking it out, rinse it repeatedly with deionized water 3 times and dry it in a drying oven at 110℃ for 2 hours.
[0027] Preparation of bissilane coupling agent hydrolysis solution: BTSE and BSA are compounded at a mass ratio of 2:1, i.e., 1.67 g of BTSE (1,2-bis(triethoxysilyl)ethane) and 0.83 g of BSA (bis[3-(trimethoxysilyl)propyl]amine) are weighed and dissolved in 100 mL of 75% (v / v) ethanol aqueous solution. The pH is adjusted to 4.0 with glacial acetic acid, and the solution is stirred and hydrolyzed for 60 minutes at room temperature of 25°C to obtain a 2.5 wt% bissilane coupling agent hydrolysis solution.
[0028] Pretreatment with bissilane coupling agent: The dried quartz fiber electronic cloth is completely immersed in the prepared bissilane coupling agent hydrolysis solution, soaked at room temperature for 30 minutes, taken out and drained, and then placed in a 120℃ drying oven for heat treatment for 1.5 hours.
[0029] Plasma surface activation: The pretreated quartz fiber electrons are arranged in the reaction chamber of the radio frequency plasma treatment device, the vacuum is evacuated to 50 Pa, argon gas is introduced as the working gas, the radio frequency power is set to 200W, and the plasma treatment time is 20 minutes.
[0030] Resin composite: The plasma-treated quartz fiber electronic cloth is fully impregnated in bisphenol A type epoxy resin, and 8 layers are laid. The vacuum bag compression molding process is used, and the mixture is pre-cured at 80°C for 2 hours, and then post-cured at 120°C for 3 hours to obtain an interface-reinforced high-purity quartz fiber electronic cloth / epoxy resin composite laminate.
[0031] Example 2 Quartz fiber electronic cloth cleaning pretreatment: Same as in Example 1.
[0032] Preparation of bissilane coupling agent hydrolysis solution: Weigh 2.5 g of BTSE, dissolve it in 100 mL of 75% (v / v) ethanol aqueous solution, adjust the pH to 3.5 with glacial acetic acid, and stir and hydrolyze at 15℃ for 90 minutes to obtain a 2.5 wt% bissilane coupling agent hydrolysis solution.
[0033] Pretreatment with bissilane coupling agent: The dried quartz fiber electronic cloth is completely immersed in the prepared bissilane coupling agent hydrolysis solution, soaked at room temperature for 10 minutes, taken out and drained, and then placed in an 80℃ drying oven for heat treatment for 3 hours.
[0034] Plasma surface activation: The pretreated quartz fiber electrons are arranged in the reaction chamber of the radio frequency plasma treatment device, the vacuum is evacuated to 50 Pa, argon gas is introduced as the working gas, the radio frequency power is set to 100W, and the plasma treatment time is 30 minutes.
[0035] Resin composite: The plasma-treated quartz fiber electronic cloth is fully impregnated in bisphenol A type epoxy resin, and 8 layers are laid. The vacuum bag compression molding process is used, and the mixture is pre-cured at 80°C for 2 hours, and then post-cured at 120°C for 3 hours to obtain an interface-reinforced high-purity quartz fiber electronic cloth / epoxy resin composite laminate.
[0036] Example 3 Quartz fiber electronic cloth cleaning pretreatment: Same as in Example 1.
[0037] Preparation of bissilane coupling agent hydrolysis solution: Weigh 2.5 g of BSA, dissolve it in 100 mL of 75% (v / v) ethanol aqueous solution, adjust the pH to 5.0 with glacial acetic acid, and stir and hydrolyze at 40℃ for 30 minutes to obtain a bissilane coupling agent hydrolysis solution with a concentration of 2.5 wt%.
[0038] Pretreatment with bissilane coupling agent: The dried quartz fiber electronic cloth is completely immersed in the prepared bissilane coupling agent hydrolysis solution, soaked at room temperature for 60 minutes, taken out and drained, and then placed in a 150℃ drying oven for heat treatment for 0.5 hours.
[0039] Plasma surface activation: The pretreated quartz fiber electrons are arranged in the reaction chamber of the radio frequency plasma treatment device, the vacuum is evacuated to 50 Pa, argon gas is introduced as the working gas, the radio frequency power is set to 300W, and the plasma treatment time is 10 minutes.
[0040] Resin composite: The plasma-treated quartz fiber electronic cloth is fully impregnated in bisphenol A type epoxy resin, and 8 layers are laid. The vacuum bag compression molding process is used, and the mixture is pre-cured at 80°C for 2 hours, and then post-cured at 120°C for 3 hours to obtain an interface-reinforced high-purity quartz fiber electronic cloth / epoxy resin composite laminate.
[0041] Example 4 The preparation method of this embodiment is basically the same as that of Example 1, except that in step 2, the concentration of the hydrolysis solution of the bissilane coupling agent is 1 wt%, that is, 0.67 g of BTSE and 0.33 g of BSA are weighed.
[0042] Example 5 The preparation method of this embodiment is basically the same as that of Example 1, except that in step 2, the concentration of the bissilane coupling agent hydrolysis solution is 3wt%, that is, 2 g of BTSE and 1 g of BSA are weighed.
[0043] Comparative Example 1 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 2, the concentration of the bissilane coupling agent hydrolysis solution is 0.8wt%, that is, 0.53 g of BTSE and 0.27 g of BSA are weighed.
[0044] Comparative Example 2 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 2, the concentration of the bissilane coupling agent hydrolysis solution is 3.5 wt%, that is, 2.33 g of BTSE and 1.17 g of BSA are weighed.
[0045] Example 6 The preparation method of this embodiment is basically the same as that of Example 1, except that in step 2, BTSE and BSA are compounded in a mass ratio of 1:1, that is, 1.25 g of BTSE is weighed.
[0046] Example 7 The preparation method of this embodiment is basically the same as that of Example 1, except that in step 2, BTSE and BSA are compounded in a mass ratio of 3:1, that is, 1.88 g of BTSE is weighed.
[0047] Comparative Example 3 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 2, BTSE and BSA are compounded at a mass ratio of 0.8:1, that is, 1.11 g of BTSE is weighed.
[0048] Comparative Example 4 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 2, BTSE and BSA are compounded in a mass ratio of 3.5:1, that is, 1.94 g of BTSE is weighed.
[0049] Comparative Example 5 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 2, the compounded BTSE and BSA are replaced with 2.5 wt% of monosilane KH-560 (γ-glycidoxypropyltrimethoxysilane).
[0050] Comparative Example 6 The preparation method of this comparative example is basically the same as that of Example 1, except that: the quartz fiber electronic cloth was not pretreated with a bissilane coupling agent, and the quartz fiber electronic cloth was directly activated by plasma surface treatment under the same conditions as in Example 1.
[0051] Comparative Example 7 The preparation method of this comparative example is basically the same as that of Example 1, except that: the quartz fiber electronic cloth was not subjected to plasma surface activation, and it was directly compounded with resin after pretreatment with bissilane coupling agent, and the treatment conditions were the same as those in Example 1.
[0052] Comparative Example 8 The preparation method of this comparative example is basically the same as that of Example 1, except that the quartz fiber electronic cloth was not pretreated with a silane coupling agent and activated by plasma, but was directly compounded with the resin matrix. The other conditions are the same as those of Example 1.
[0053] Comparative Example 9 The preparation method of this comparative example is basically the same as that of Example 1, except that the process order of steps 3 and 4 is reversed. The quartz fiber electronic cloth is first subjected to plasma treatment and then impregnated with a bissilane coupling agent. The treatment conditions are the same as those in Example 1.
[0054] Comparative Example 10 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 4, the plasma activation treatment time is 8 minutes.
[0055] Comparative Example 11 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 4, the plasma activation treatment time is 40 min.
[0056] Performance testing: The interfacial shear strength (ILSS) of the composite laminates prepared in the examples and comparative examples was tested using the short beam shear test method. The dielectric constant (Dk) and dielectric loss factor (Df) were measured at a frequency of 10 GHz. The results are shown in Table 1.
[0057] Table 1
[0058] As shown in Table 1, the ILSS of Example 1 of this invention reached 48.5 MPa, which is 375% higher than the control without silane pretreatment and plasma activation (Comparative Example 8, 10.2 MPa); 113% higher than plasma treatment only (Comparative Example 6, 22.8 MPa); 41% higher than silane treatment only (Comparative Example 7, 34.5 MPa); and 89% higher than conventional single silane KH-560 and plasma treatment (Comparative Example 5, 25.6 MPa). This demonstrates that the scheme of pretreatment with dual silane coupling agents combined with plasma activation has a significant synergistic effect, far superior to single treatment or conventional single silane pretreatment schemes. Meanwhile, while significantly enhancing interfacial bonding, this invention does not sacrifice the inherent low dielectric loss advantage of quartz fiber electronic cloth. Compared with the control without silane pretreatment and plasma activation (Df 0.0095), Df is reduced by 49%, and compared with plasma treatment only (Df 0.0088), Df is reduced by 45%. This indicates that the three-dimensional cross-linked interfacial layer constructed by this invention effectively fills the voids at the fiber-resin interface, reduces interfacial polarization loss, and plasma activation does not introduce excessive polarity residue.
[0059] Comparative Example 5 used a conventional monosilane, KH-560, whose ILSS (25.6 MPa) and Df (0.0060) were significantly inferior to the bissilane system of the present invention (Example 1). This demonstrates that the three-dimensional Si-O-Si crosslinked network formed by the BTSE / BSA bissilane has unique advantages in interface enhancement and low loss.
[0060] The ILSS of Comparative Example 9 (plasma followed by silane treatment) was only 36.8 MPa, far inferior to that of Example 1. This indicates that chemical grafting of silane coupling agents must be performed before plasma physical activation. Pre-activation introduces polar groups, but subsequent wet silane treatment can cover or destroy these active sites, leading to synergistic failure.
[0061] When the total concentration of the bissilane coupling agent is too low (0.8 wt%, Comparative Example 1), the coupling layer is incomplete, resulting in a decrease in ILSS and an increase in Df. When the concentration is too high (3.5 wt%, Comparative Example 2), the coupling agent self-condenses to form a weak interface layer, which deteriorates both ILSS and dielectric properties. An imbalance in the ratio of BTSE to BSA (Comparative Examples 3 and 4) disrupts the balance between crosslinking density and reactivity, leading to a decrease in performance. Insufficient plasma treatment time (8 min, Comparative Example 10) results in inadequate activation, with ILSS only reaching 30.4 MPa. Excessive treatment time (40 min, Comparative Example 11) leads to excessive etching, damaging the coupling layer, causing ILSS to drop to 22.3 MPa and Df to rise to 0.0079.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing high-purity quartz fiber electronic cloth, characterized in that, Includes the following steps: S1, immerse the quartz fiber electronic cloth in a silane coupling agent hydrolysis solution, remove it and perform heat treatment to obtain the pretreated quartz fiber electronic cloth; S2, the pretreated quartz fiber electronic cloth is subjected to plasma treatment; S3 involves combining plasma-treated quartz fiber electronic cloth with a resin matrix to obtain high-purity quartz fiber electronic cloth.
2. The method for preparing high-purity quartz fiber electronic cloth as described in claim 1, characterized in that: In step S1, the components of the silane coupling agent hydrolysis solution include one or both of BTSE and BSA.
3. The method for preparing high-purity quartz fiber electronic cloth as described in claim 2, characterized in that: The total mass concentration of silane coupling agent in the hydrolysis solution of the silane coupling agent is 1~3wt%.
4. The method for preparing high-purity quartz fiber electronic cloth as described in claim 3, characterized in that: The mass ratio of BTSE to BSA in the silane coupling agent hydrolysis solution is 1~3:
1.
5. The method for preparing high-purity quartz fiber electronic cloth as described in claim 2, characterized in that: The preparation of the hydrolyzed solution of the bissilane coupling agent includes the step of adding the silane coupling agent to an ethanol solution for hydrolysis.
6. The method for preparing high-purity quartz fiber electronic cloth as described in claim 5, characterized in that: The pH of the alcohol-water mixed solvent is 3.5-5.0, and the hydrolysis conditions are hydrolysis at 15-40℃ for 30-90 min.
7. The method for preparing high-purity quartz fiber electronic cloth as described in claim 1, characterized in that: In step S1, the quartz fiber electronic cloth also undergoes cleaning pretreatment and drying treatment; the heat treatment temperature is 80~150℃ and the time is 0.5~3h.
8. The method for preparing high-purity quartz fiber electronic cloth as described in claim 1, characterized in that: In step S2, the plasma treatment includes arranging pretreated quartz fiber electrons in a plasma treatment device, introducing a working gas under a vacuum of 1~1000 Pa, and performing plasma treatment with a treatment power of 100~300W and a time of 10~30min.
9. The method for preparing high-purity quartz fiber electronic cloth as described in claim 1, characterized in that: In step S3, the resin matrix includes any one of epoxy resin, cyanate ester resin, silane-containing resin, bismaleimide resin, and polyimide resin.
10. A high-purity quartz fiber electronic cloth, characterized in that: It is prepared by the preparation method of high-purity quartz fiber electronic cloth according to claims 1 to 9.